Estudo da bioacessibilidade in vitro de carotenoides microalgais - Pinheiro, Pricila Nass (2020)
Microalgal biomass is a proven source of bioactive compounds with an emphasis on carotenoids. However, there is great concern about the influence of the microalgal matrix on the bioactive structures bioaccessibility. In this sense, this study aimed to investigate the carotenoids bioaccessibility from three different products: whole dried biomass (WDB), wet ultrasonicated biomass (WUB); and isolated carotenoids extract (ICE) from two commercial microalgae species Chlorella vulgaris and Spirulina sp. The samples were submitted to in vitro digestion model according to the INFOGEST protocol. Carotenoids were determined by HPLC-PDA-MS/MS. A total of twenty-two different carotenoids were separated in the control extracts, the major ones being all-trans-lutein (48.1%) for C. vulgaris and all-trans-β-carotene (29.3%) in the Spirulina. After in vitro digestion, for C. vulgaris, six compounds were bioaccessible in WDB, nine in WUB and ICE. The 5,6:5’,6’-diepoxy-β-carotene was the most bioaccessible carotenoid in all products (WDB 18.3%; WUB 22.6%; and ICE 29.8%). On the other hand, for the Spirulina species, six carotenoids were bioaccessible in WDB, ten in WUB and ICE. All-trans-β-cryptoxanthin showed the highest bioaccessibility (46.8%) in WDB, while all-trans-cantaxanthin in WUB (99.5%) and ICE (95.5%). Finally, the results showed the significant influence of the nature of the product in promoting the bioaccessibility of microalgal carotenoids, since total bioaccessibility improved for both species according to the type of product (ICE>WUB>WDB). Thus, the data suggest that the bioaccessibility of ICE carotenoids is greater than in WDB and WUB. Therefore, ICE should be considered a product that provides bioavailable carotenoids and could be the best choice, such as ingredients in the development of functional foods carotenoids-based.